Nosocomial infections surveillance in the Surgical and Neurological Intensive Care Units of Firat Medical Center in year 2003 - Celik, Ilhami; Demirdag, Kutbettin; Denk, Affan; Akbulut, Ayhan; Kilic, S. Sirri (Aves, 2006)
Intensive care units (ICU) have more risk of nosocomial infections (NIs) and they contribute significantly to morbidity and mortality. The aim of this study was to determine the rates of hospital-acquired infections, infection sites and infectious agents in patients who were hospitalized and followed-up at Firat Medical Center's Surgical (SICU) and Neurological Intensive Care Units (NICU) between January 1-December 31, 2003. Episodes of NIs were detected in 13.3% of the patients hospitalized at SICU and 31.3% of the patients hospitalized at NICU. NI that was the most frequently observed in NICU was urinary tract infection (UTI) (62.5%) and pneumonia (63.6%) in SICU. The most frequently isolated agents in SICU were Pseudomonas spp. (27.1%), coagulase-negative staphylococci (CoNS) (24%), S. aureus (21.9%), and Acinetobacter baumannii (19.8%) in SICU whilst these were Escherichia coli (40%), CoNS (18.2%), Staphylococcus aureus (18.2%) and Pseudomonas spp. (14.5%) in NICU. While E. coli was the most common infectious agent that caused UTI in both units, S. aureus was found to be the agent most frequently responsible for pneumonia. The rate of Candida spp. isolates was 17.8% in both ICUs. As a result, NI rate was found to be 2.5 fold higher in NICU than in SICU. Increasing episodes of NIs due to Candida spp. recently became more striking in our hospital's ICUs. Fastidious surveillance of NIs and identification of the responsible microorganisms would provide guidance to begin optimum empirical antibiotic therapy which would lead decline in morbidity, mortality and cost.
Keywords: Intensive care units; nosocomial infections; surveillance